Optimizing Dairy Cow Performance: Influence of Fortified Urea Molasses Mineral Block on Milk Yield in Winter - , Tanzeela Tabasum; , Aaqib Rashid khan; , Parvaiz Ahmad Reshi; , Muteeb Ullah Rafique (Archives of Current Research International, 2025)
The article is good contribution to refresh cost effective feed supplementation strategies especially to cater climate effect. This study evaluated the effect of urea-molasses mineral blocks (UMMBs), with or without enzyme and herb enrichment, on the milk yield and composition of dairy cows during the winter months in two phases. In Phase 1, experimental multinutrient blocks were prepared, and dairy cows were grouped based on body weight, stage of lactation, milk yield, and parity. In Phase 2, animals were offered UMMBs, and milk samples were collected. Milk yield was recorded daily, while milk composition was analyzed at three points: the start of the experiment, mid-trial, and at the end of the experiment (days 0, 22, and 45). Milk yield increased in the treatment groups compared to the control group, where it declined during the experimental period (December to February). However, this increase was not statistically significant. The highest milk production was recorded in T4 (Urtica dioica + enzyme-enriched UMMB), while the lowest was in T0 (control group). A significant (P<0.05) increase in milk protein percentage was observed in all treatment groups compared to the control, with the highest protein percentage in T4 (Urtica dioica + enzyme-fortified UMMB) and the lowest in T1 (control group). Although milk fat percentage and 3.5% fat-corrected milk (FCM) increased in all treatment groups compared to the control, the differences were not statistically significant. However, milk solids-not-fat (SNF) percentage was significantly (P<0.05) higher in T4 compared to other treatment and control groups. Additionally, milk lactose percentage was significantly (P<0.05) higher in T1 and T4 than in T0 (control group). This study highlights the importance of UMMB supplementation in sustaining milk production and composition during winter forage scarcity. It suggests that enzyme- and herb-enriched UMMBs can enhance milk yield, protein, and SNF content in dairy cows. The findings of the study provide valuable insights for optimizing ruminant nutrition and improving dairy performance in harsh climates.